2016
DOI: 10.1111/jgh.13388
|View full text |Cite
|
Sign up to set email alerts
|

Role of splenic reservoir monocytes in pulmonary vascular monocyte accumulation in experimental hepatopulmonary syndrome

Abstract: Background and AimPulmonary monocyte infiltration plays a significant role in the development of angiogenesis in experimental hepatopulmonary syndrome (HPS) after common bile duct ligation (CBDL). Hepatic monocytes are also increased after CBDL, but the origins remain unclear. Splenic reservoir monocytes have been identified as a major source of monocytes that accumulate in injured tissues. Whether splenic monocytes contribute to monocyte alterations after CBDL is unknown. This study evaluates monocyte distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Our results suggest that skin-infiltrating monocytes in scleroderma are recruited from the entire periphery and not, as previously suggested (Egawa et al, 2013), exclusively from the bone marrow. We could show that cells in dermal lesions are recruited from the splenic reservoir, as has also been shown for acute tissue damage (Wu et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Our results suggest that skin-infiltrating monocytes in scleroderma are recruited from the entire periphery and not, as previously suggested (Egawa et al, 2013), exclusively from the bone marrow. We could show that cells in dermal lesions are recruited from the splenic reservoir, as has also been shown for acute tissue damage (Wu et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Recruited monocytes are generally considered to be derived from progenitor cells in the bone marrow that migrate to the site of injury. However, a recent study found that splenic reservoir monocytes contribute to pulmonary monocyte accumulation in experimental HPS . Splenectomy decreased pulmonary monocyte influx and improved gas exchange but increased hepatic monocyte levels and significantly worsened liver function …”
Section: Pathogenesis Of Hps: Lessons From Experimental Modelsmentioning
confidence: 96%
“…However, a recent study found that splenic reservoir monocytes contribute to pulmonary monocyte accumulation in experimental HPS. (30) Splenectomy decreased pulmonary monocyte influx and improved gas exchange but increased hepatic monocyte levels and significantly worsened liver function. (30) One trigger for pulmonary intravascular monocyte accumulation appears to be bacterial translocation from the gut into the portal circulation.…”
Section: Monocyte Infiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pieces of liver tissues were fixed in 4% formaldehyde for 24 h. Paraffin sections (5μm) were prepared and subjected to haematoxylin and eosin staining for general morphological observations. Masson Trichrome staining was performed according to Wu's report (Wu, Zhang, Yang, Hu, & Fallon, 2016). The images were captured using a light microscope (Nikon Eclipse TE2000-U, NIKON, Japan) and then photographed at 200× magnification.…”
Section: Histopathological Examinationmentioning
confidence: 99%